BATIK MOTIF BABARAN AGUNG: Proses Penciptaan dan Aplikasinya pada Ready to Wear Deluxe - Putri, Adestya Rahmana; Suharno, Suharno; marlianti, Mira (Institut Seni Indonesia Padangpanjang, 2024)
This article is based on the empirical experience of the author in creating the Babaran Agung batik pattern at the Sekar Ayu Batik Studio in Tuban, East Java, in 2023. The process of creating this batik pattern involved an academic approach supported by a studio approach. The academic approach refers to a systematic process that must involve scientific principles in the creation of the batik pattern, while the studio approach emphasizes practicality, though not entirely. The combination of these two approaches has not been found by the creator in various references regarding the process of creating batik pattern. Therefore, the purpose of this writing is to enrich the concept of batik motif creation by combining academic elements supported by a studio approach. Methodologically, the creation of this batik motif was carried out through three stages: exploration, design, and realization, each of which involved the studio approach. The result of the creation is a hand-drawn batik fabric with the Babaran Agung motif, applied to ready-to-wear deluxe items and presented at the Jakarta Muslim Fashion Week (JMFW) 2023.